EFEKTIVITAS KONSELING KELOMPOK PENDEKATAN REBT TERHADAP PENYESUAIAN DIRI ANAK BINAAN DI LPKA - Ratna, Elsa Dwi; Yuline, Yuline; Halida, Halida (Universitas Tanjungpura, 2025)
This article reviews to determine the effectiveness of group counseling using the REBT (Rational Emotive Behavior Therapy) approach in improving self-adjustment among juvenile detainees at LPKA Class II Sungai Raya. The research method used is an experimental pre-experimental design, specifically a one group pretest and posttest design. Total of 6 detainees with the lowest self-adjustment scores were selected through purposive sampling from a population of 22 detainees, using non-probability sampling techniques. The analysis results, using an independent sample t-test, showed a significant difference between the pre-test and post-test scores. The average post-test self-adjustment score reached 122, which was higher than the average pre-test score of 59.67. With a Sig. (2-tailed) value of 0.000 < 0.05, this result proves that group counseling with the REBT approach has a positive impact and significant changes for the detainees, thus confirming the hypothesis. It can be concluded that group counseling using the REBT approach is effective in improving self-adjustment among juvenile detainees at LPKA Class II Sungai Raya.